Methylamine as a nitrogen source for microorganisms from a coastal marine environment. (29th March 2017) - Taubert, Martin; Grob, Carolina; Howat, Alexandra M.; Burns, Oliver J.; Pratscher, Jennifer; Jehmlich, Nico; von Bergen, Martin; Richnow, Hans H.; Chen, Yin; Murrell, J. Colin
Summary: Nitrogen is a key limiting resource for biomass production in the marine environment. Methylated amines, released from the degradation of osmolytes, could provide a nitrogen source for marine microbes. Thus far, studies in aquatic habitats on the utilization of methylamine, the simplest methylated amine, have mainly focussed on the fate of the carbon from this compound. Various groups of methylotrophs, microorganisms that can grow on one‐carbon compounds, use methylamine as a carbon source. Non‐methylotrophic microorganisms may also utilize methylamine as a nitrogen source, but little is known about their diversity, especially in the marine environment. In this proof‐of‐concept study, stable isotope probing (SIP) was used to identify microorganisms from a coastal environment that assimilate nitrogen from methylamine. SIP experiments using 15 N methylamine combined with metagenomics and metaproteomics facilitated identification of active methylamine‐utilizing Alpha‐ and Gammaproteobacteria. The draft genomes of two methylamine utilizers were obtained and their metabolism with respect to methylamine was examined. Both bacteria identified in these SIP experiments used the γ‐glutamyl‐methylamide pathway, found in both methylotrophs and non‐methylotrophs, to metabolize methylamine. The utilization of 15 N methylamine also led to the release of 15 N ammonium that was used as nitrogen source by other microorganisms not directly using methylamine.